GEOLOGI DAN GENESA BENTONIT DI DESA PUNUNG, KECAMATAN PUNUNG, KABUPATEN PACITAN, PROVINSI JAWA TIMUR - , HYACINTHA DIAN TATIWI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Bentonite is one type of clay minerals which have montmorilonite content 85 weight %. Minerals commonly found in bentonite to consist of montmorilonite and often contain variable of accessory cristal grains that were originally phenocrysts in the volcanic glass. These minerals are feldspar (commonly orthoclase and oligoclase), biotite, quartz, pyroxene and zirkon. Bentonite exposed in Pacitan is wide enough, one of them exposed at Punung Subdistric, Pacitan Regency, East Java Province. The methodology of this study are petrographic, X-Ray Diffraction and swelling analysis. Punung bentonite is alterated from glassy material (tuff) in clay unit. Bentonite is rich in mineralogy characteristic by smectite montmorillonite. Based on swelling capability, type of Punung bentonite is Ca-bentonite. Punung bentonite formed by hydrothermal activity and devitrification.